Elastogenesis in Adult Cells: The Surprising Relationship to Alzheimer's Disease, and Implications for Tissue Engineering. - Saitow, Cassandra. (2017)
Abstract: Elastic fibers are critical for mechanical integrity of extensible organs such as lungs, skin, and blood vessels. Elastin expression is limited to early developmental stages, as the protein has an extremely long half-life and can therefore persist for the lifetime of the animal. Thus, complications arise in the event of disease or injury, as mechanically sound elastic fibers are not produced by adult cells. In this dissertation, I address the challenge of inducing elastin fibers in adult smooth muscle cells, with the goal of promoting elastic fiber deposition upon recellularization of silk vascular grafts. In the first part of my dissertation research, I found that treatment of adult human smooth muscle cells with heparin induces elastin deposition in the extracellular space.1 Upon further investigation, certain cells were demonstrated to be strongly responsive to heparin, whereas others were not. One common characteristic of "responder" cells was that they were derived from Alzheimer's Disease (AD) patients. At least four AD and four non-demented control (NDC) cell lines were tested, indicative of a statistically nonrandom association between AD status and elastogenicity. This led me to hypothesize that one of the disrupted signaling networks involved in the pathogenesis of AD may also induce a permissive environment for heparin-induced elastogenesis in adult AD-derived cells. To reveal the specific mechanism driving heparin-induced elastogenesis, we compared NDC and AD cells, both untreated and heparin treated, using microarray analysis. Of the observed changes, insulin-like growth factor-1 (IGF-1) signaling was one of the most significantly different between AD and NDC cell types. Disruptions in IGF-1 homeostasis have been linked to both AD and extracellular matrix remodeling. Thus, the next step in this project will be to analyze IGF signaling components and transcription factors to determine if this pathway is indeed involved. In addition to the discovery of an AD connection to elastin, I also demonstrate that heparinized silk films are able to induce the same elastogenic response as with soluble heparin. This novel finding has implications for development of a heparinized, silk-based vascular graft, resistant to thrombosis and restenosis, while promoting appropriate remodeling of the extracellular matrix following implantation.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisors: John Castellot, and David Kaplan.; Committee: Ira Herman, Catherine Kuo, Lauren Black, III, and Mark Iafrati.; Keywords: Cellular biology, and Biomedical engineering.